Diagnostic of preliminary breakdown in an artificial thunderclouds - Bidin, Noriah; Pangeran, Madia (Penerbit UTM Press, 2003)
Lightning is a destructive phenomenon. It can cause fire, damage and electrocute human being and animal. Therefore, we need to have some kinds of protective devices to trigger lightning before it could strike naturally. One way of doing it is by using laser. In this study unfocused UV laser was used to actively discharge the electrodes. Electrodes are used to represent thunderclouds. The separation distance between the electrodes was adjusted to determine the condition for preliminary breakdown. The result showed that, preliminary breakdown occurred at a short ranges separation distance of electrodes, hence very high electric field is required. The breakdown is found stimulated by interfering a UV laser in the thunderclouds. In this respect, the separation distance for breakdown is triple that of without laser. Hence minimum electric field can be achieved for such occurrence of preliminary breakdown.